Binding activity and specificity of tail fiber protein 35Q for Salmonella pullorum - Deng, Hewen; Feng, Linwan; Shi, Kun; Du, Rui (Frontiers in Microbiology, 2024)
Salmonella, a prevalent pathogen with significant implications for the poultry industry and food safety, presents a global public health concern. The rise in antibiotic resistance has exacerbated the challenge of prevention. Accurate and sensitive detection methods are essential in combating Salmonella infections. Bacteriophages, viruses capable of targeting and destroying bacteria, leverage their host specificity for accurate microbial detection. Notably, the tail fiber protein of bacteriophages plays a crucial role in recognizing specific hosts, making it a valuable tool for targeted microbial detection. This study focused on the tail fiber protein 35Q of Salmonella pullorum (SP) bacteriophage YSP2, identified through protein sequencing and genome analysis. Bioinformatics analysis revealed similarities between 35Q and other Salmonella bacteriophage tail fiber proteins. The protein was successfully expressed and purified using an Escherichia coli expression system, and its binding activity and specificity were confirmed. ELISA assays and adsorption experiments demonstrated that 35Q interacts with the outer membrane protein (OMP) receptor on bacterial surfaces. This investigation provides valuable insights for targeted Salmonella detection, informs the development of specific therapeutics, and enhances our understanding of the interaction between Salmonella bacteriophages and their hosts.